2010
DOI: 10.1021/ie100333v
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Biological and Electrochemical Oxidation Treatment for High Toxicity Pesticide Pollutant

Abstract: A novel integrated biological and electrochemical oxidation (BEO) process was proposed for the treatment of biorefractory pesticide wastewater with high toxicity. An acetamiprid solution of 1000 mg L -1 was used as the target pollutant. Its biodegradability in terms of biochemical oxygen demand in a 5-d test period (BOD 5 )/ total organic carbon (TOC) was only 0.0057, presenting its high biorefractory property. In the BEO system with boron-doped diamond electrode (BDD), the value of BOD 5 /TOC was improved to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…In recent years, the combined processes, in particular physicochemical and biological combined treatments, have received a growing attention for their efficiency to achieve complete mineralization of biorecalcitrant compounds with the objective to reduce operating costs [1][2][3][4][5][6][7][8][9][10][11][12]. In such systems, a physicochemical pretreatment such as an advanced oxidation process (AOP) or an electrochemical method is used to change the structure of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the combined processes, in particular physicochemical and biological combined treatments, have received a growing attention for their efficiency to achieve complete mineralization of biorecalcitrant compounds with the objective to reduce operating costs [1][2][3][4][5][6][7][8][9][10][11][12]. In such systems, a physicochemical pretreatment such as an advanced oxidation process (AOP) or an electrochemical method is used to change the structure of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…It suggested that these two newly isolated bacteria may resist the toxicity of some neonicotinoid insecticides during the nicotinedegrading process, which would have practical implications for tobacco waste bio-treatment. Neonicotinoids are not readily degraded and are considered as biorefractory pesticide pollutants (Tomizawa and Casida 2005;Liu et al 2010), and only limited microbial species have been reported to transform neonicotinoid insecticides (Dai et al 2010a, b). However, maybe because neonicotinoids have a structural similarity to nicotine (Tomizawa and Casida 2005), nicotine-degrading bacteria TW and TY showed ability to degrade the tested neonicotinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Upon now, three-dimensional electrode technology has been http://dx.doi.org/10.1016/j.seppur.2015. 10.053 1383-5866/Ó 2015 Elsevier B.V. All rights reserved. successfully used to remove metal ions [21], cyanide [22], and dyes [23] from wastewater.…”
Section: Introductionmentioning
confidence: 98%
“…2-Diethylamino-6-methyl-4-hydroxy pyrimidine (DTMHP) is a typical pesticide intermediate widely used in agricultural, i.e., it is the main raw material for the synthesis of diazinon [3] and pirimiphos methyl [4], which are biorefractory and microtoxic. Recently, many methods have been used to treat this kind of wastewater, such as Fenton's reagent [5,6], photocatalysis [7][8][9], biological techniques [10,11] and electrochemical degradation [12,13]. However, Fenton's reagent will produce a large number of chemical sludge.…”
Section: Introductionmentioning
confidence: 99%